REPRESENTASI FEMINISME TOKOH IBU DALAM NOVEL AYAH KARYA ANDREA HIRATA - Anggi S. Nome; Karolus B. Jama; Margareta P.E Djokaho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study focuses on the representation of feminism in Andrea Hirata’s novel Ayah, based on the following research questions: 1) How is feminism represented through the mother character’s dialogue in Andrea Hirata’s novel Ayah? 2) How is feminism represented through the mother character in Andrea Hirata’s novel Ayah? The objective of this study is to analyze the representation of feminism through the dialogue and characterization of the mother figure in the novel Ayah by Andrea Hirata. The theory used in this study is Simone Beauvoir’s Existentialist Feminism. The method used in this study is a qualitative descriptive method. The results of the study indicate that, through the author’s portrayal, the mother character has achieved her freedom through the three steps outlined by Simone Beauvoir: Mainstreaming, Empowerment, and Equality. This study describes feminism, which addresses gender equality between women and men, as demonstrated through the mother character in the author’s representation. This indicates that women are capable of achieving the freedom they desire through the three stages one must undergo to attain freedom: voicing freedom, living independently, and achieving equality with men in societal life. The mother character successfully navigates all these stages, demonstrating that women are shaped by their environment and are capable of transforming social structures.